Strategies to Improve Patient Flow in the Emergency Department during the COVID-19 Pandemic: A Narrative Review of Our Experience - Ali S. Al-Shareef; Azzah Al Jabarti; Kholoud A. Babkair; Maan Jamajom; Abduallah Bakhsh; Syed Sameer Aga (Emergency Medicine International)
Objective. The COVID-19 pandemic has resulted in a tremendous strain on the global healthcare system. Emergency departments worldwide have been challenged to the extreme end. This has led clinicians and policy creators to rearrange patient flow pathways for an efficient emergency department (ED). Methods. It was reported according to our experience of utilizing a novel strategy to enhance patient flow while reducing the risk of infection transmission among patients and healthcare staff. This included the development of three layers of triage. First, an outer checkpoint prior to the hospital entrance was established to identify eligible patients for emergency department visits. The second layer of triage is located at the ED entrance to direct patients either to the respiratory or nonrespiratory care area to identify potentially infected patients and the third is the routine full triage activity. Then, after completing a clinical assessment in the ED, physicians determine the need for an inpatient isolation unit, a nonisolation inpatient unit, or discharge. Moreover, examples of additional measures were substantial changes to shift schedules; rerouting ambulance crews with COVID patients to inpatient beds directly bypassing the ED; controlled use of personal protective equipment (PPE); and implementing appropriate COVID-19 screening tests. Results. During the peak of the pandemic, our strategies achieved favorable results and minimized unnecessary ED visits without any patient complications. Conclusion. This current study provides a set of newly developed steps and procedures that can be further control patient flow pathways and maintain a low risk of infection transmission to a manageable level for an efficient ED.